Monodisperse tin nanoparticles and hollow tin oxide nanospheres as anode materials for high performance lithium ion batteries. Issue 2 (3rd January 2019) - Zhao, Xixia; Wang, Wenhui; Hou, Zhen; Yu, Yikang; Di, Qian; Wu, Xiaotong; Wei, Guijuan; Quan, Zewei; Zhang, Jun
Abstract : Monodisperse Sn nanoparticles and hollow/amorphous SnO x nanospheres are prepared via a facile colloidal method, and they exhibit good electrochemical performances as anode materials in lithium ion batteries. Abstract : Sn-Based materials are considered as promising anode materials for lithium ion batteries due to their high theoretical capacities; however, aggregation of electrochemically active particles and pulverization resulting from huge volume changes during alloying/dealloying severely limit their performance. To solve these problems, nanosized and hollow structures have been proposed. Herein, uniform solid Sn nanoparticles and hollow/amorphous SnO x nanospheres are prepared accordingly and their electrochemical performances as anode materials in lithium ion batteries have been evaluated. Uniform solid Sn nanoparticles deliver a capacity of 416.4 mA h g −1 for 400 cycles at a current of 500 mA g −1, corresponding to a high capacity retention of 81.1%. Furthermore, hollow/amorphous SnO x nanospheres show a high capacity retention of 81.3% for 400 cycles at a current of 500 mA g −1 and exhibit a good rate capability (retains 58.0% of the capacity at 1000 mA g −1 with respect to 100 mA g −1 ). It is believed that their good electrochemical performances mainly originate from their small sizes (<20 nm) and unique nanoarchitectures.